Elsewhere - Russo, Richard, 1949- (Alfred A. Knopf, 2012)
After eight commanding works of fiction, the Pulitzer Prize winner now turns to memoir in a hilarious, moving, and always surprising account of his life, his parents, and the upstate New York town they all struggled variously to escape.